PELATIHAN PENGGUNAAN APLIKASI REFERENSI UNTUK MENUNJANG PENULISAN AKADEMIS BAGI MAHASISWA PENDIDIKAN BAHASA INGGRIS - Sumarni Sumarni; Eka Fajar Rahmani; Eusabinus Bunau; Rahayu Apriliaswati; Eni Rosnija; Luwandi Suhartono (As-Sidanah, 2023)
The public service activity was carried out as a workshop aimed at helping English Education students, especially semester 6, in writing citations and bibliographies using the Mendeley application. The activity was carried out for one day, starting at 07.30-17.00 WIB with five sessions, each held for 60 to 95 minutes. The activity participants were 43 English Education students from 3 different institutions. The method used in implementing the public service activity was Participatory Action Research (PAR) where the participants were the center of the activityThe results of the analysis showed that the training activities went smoothly and very well, the students participated enthusiastically during the activity. The indicators of the success are shown from the five (5) indicators including (1) significantly increasing participants' ability to write citations and bibliography; (2) the running of activities in accordance with the plan is effective and efficient; (3) the enthusiasm of participants that exceeds the target participants; (4) very positive responses from participants; and (5) there are suggestions to hold similar activities more often with more target participants. The authors expect that training activities like this can be carried out again and become an agenda considering the benefits to the target participants.